2000
DOI: 10.1080/00288330.2000.9516962
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and movements of brown (Salmo trutta) and rainbow trout (Oncorhynchus mykiss) in Lake Otamangakau, central North Island, New Zealand

Abstract: The post-spawning movements and distribution of 15 brown trout (Salmo trutta Linnaeus 1758) and 21 rainbow trout (Oncorhynchus mykiss Richardson, 1836) were monitored weekly between August 1996 and March 1997 in the hydro-electric reservoir, Lake Otamangakau, New Zealand, using radio-telemetry. The most frequently used areas were the vicinity of the main inflow and the channel running through the main body of the lake. After spawning, brown trout regained rapidly their usual habitat. Rainbow trout were using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
2
3
0
Order By: Relevance
“…In accordance with our results, Soto et al (2002) reported, for our study lake-inlet system, a higher frequency of larger mature (and probably older) rainbow trout in the lake and its inlet streams from May to October, with a peak in July and August. Dedual et al (2000) reported similar results in New Zealand. Movements of rainbow trout from the lake into its inlet streams to spawn have also been described widely in the Northern Hemisphere (Behnke, 1992;Crawford, 2001), New Zealand (Rosenau, 1991;Dedual et al, 2000), but only in one study in South America, southern Argentina (Sakai and Espinos, 1994).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In accordance with our results, Soto et al (2002) reported, for our study lake-inlet system, a higher frequency of larger mature (and probably older) rainbow trout in the lake and its inlet streams from May to October, with a peak in July and August. Dedual et al (2000) reported similar results in New Zealand. Movements of rainbow trout from the lake into its inlet streams to spawn have also been described widely in the Northern Hemisphere (Behnke, 1992;Crawford, 2001), New Zealand (Rosenau, 1991;Dedual et al, 2000), but only in one study in South America, southern Argentina (Sakai and Espinos, 1994).…”
Section: Discussionsupporting
confidence: 75%
“…Dedual et al (2000) reported similar results in New Zealand. Movements of rainbow trout from the lake into its inlet streams to spawn have also been described widely in the Northern Hemisphere (Behnke, 1992;Crawford, 2001), New Zealand (Rosenau, 1991;Dedual et al, 2000), but only in one study in South America, southern Argentina (Sakai and Espinos, 1994). Also, the wide period of time during which older trout (probably the bulk of spawners) are present in the inlet streams may reflect a spawning period that extends until late spring.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The strength of the selection is affected by several factors, of which prey density, prey size, quality, catchability and learning (Allen, 1988;Dahl, 1998;Reiriz, Nicieza, & Brana, 1998;Salvanes & Hart, 1998;Sweka & Hartman, 2001;Warburton, 2003) are the most important. As a consequence of this, large nutrient-rich food items may be strongly selected (Dahl, 1915;Dedual, Maxwell, Hayes, & Strickland, 2000). A secondary effect of this may be strongly reduced prey densities (McNaught et al, 1999;Pechlaner, 1984).…”
mentioning
confidence: 97%